Pengaruh Promosi, Citra Perusahaan, Kualitas Pelayanan dan Lokasi terhadap Kepuasan Konsumen pada PT Alfaria Trijaya Alfamart Panunggangan Timur - Nurmin Arianto; Sewaka Sewaka; Syabrina Fitriyani (LAP4B, 2024)
The aim of this study is to examine the impact of promotion, company image, service quality, and location on customer satisfaction at PT Alfaria Trijaya Alfamart Panunggangan Timur. Using a quantitative method, the study employed Slovin's formula for sampling, resulting in 110 respondents. Data analysis included validity and reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The findings reveal that promotion, company image, service quality, and location each have a significant influence on customer satisfaction, with determination coefficients of 29.8%, 33.3%, 32.1%, and 27.5% respectively, all passing the t-test (t count > t table). Simultaneously, these factors significantly affect customer satisfaction, as evidenced by the regression equation Y = 12.186 + 0.117X1 + 0.271X2 + 0.141X3 + 0.043X4, with a determination coefficient of 39.6% and F count > F table (18.839 > 3.080). The remaining 60.4% is attributed to other factors not examined in this study. In conclusion, promotion, company image, service quality, and location collectively have a significant impact on customer satisfaction at PT Alfaria Trijaya Alfamart Panunggangan Timur.